2002
DOI: 10.1093/clinchem/48.2.307
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin-detectable Iron Assay for Non-Transferrin-bound Iron in Hematologic Malignancies

Abstract: Background: A microwell modification of the bleomycin assay for determining non-transferrin-bound iron (NTBI) was evaluated and compared with a chelation method. Methods: The bleomycin assay reagent and sample volumes were halved, and measurements were done in microwell plates. Samples from patients treated for hematologic malignancies were studied. The chelation method was based on mobilization of NTBI with a chelator and measurement of the ultrafiltered iron-chelator complex. NTBI results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 26 publications
3
33
0
Order By: Relevance
“…Transferrin saturation (%) was calculated by the formula : serum iron (WM)/serum transferrin (g l 31 )U3.98. NTBI was measured using the bleomycin-detectable iron assay adopted for small (25 Wl) serum volumes [25]. Brie£y, bleomycin was added to serum in the presence of ascorbic acid.…”
Section: Transferrin Iron and Other Serum Assaysmentioning
confidence: 99%
“…Transferrin saturation (%) was calculated by the formula : serum iron (WM)/serum transferrin (g l 31 )U3.98. NTBI was measured using the bleomycin-detectable iron assay adopted for small (25 Wl) serum volumes [25]. Brie£y, bleomycin was added to serum in the presence of ascorbic acid.…”
Section: Transferrin Iron and Other Serum Assaysmentioning
confidence: 99%
“…Serum samples were collected coinciding with routine sampling, 0-3 d before the initiation of the chemotherapy referred to as day 0 sample, and during the first 20 d after the onset of the chemotherapy. The median number of samples per patient was 18.5 (range 16-21) in the aSCT group and 15.5 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) in the Chemo group.…”
Section: Introductionmentioning
confidence: 99%
“…NTBI probably comprises heterogeneous iron complexes which may differ in their binding to chelating agents and whose proportions may vary in different clinical conditions (Breuer et al, 2000). The bleomycin assay used in the present study measures redox-active iron and this assay has given positive results in SCT patients only when transferrin saturation exceeds 80% (von Bonsdorff et al, 2002). The disappearance of bleomycin-detectable NTBI after the apotransferrin injection indicated that the redox-active iron in the serum of SCT patients was in a form that was effectively bound by transferrin.…”
Section: Discussionmentioning
confidence: 95%
“…The bleomycin assay gives clearly lower values for NTBI than other methods based on mobilization of NTBI with a chelator, and determination of the ultrafiltered iron-chelator complex (von Bonsdorff et al, 2002). We used the bleomycin assay because it has a high specificity for NTBI and does not measure ferritin-bound iron.…”
Section: Discussionmentioning
confidence: 99%